Sympathetic Activation in Hypertensive Chronic Kidney Disease – A Stimulus for Cardiac Arrhythmias and Sudden Cardiac Death? - Márcio Galindo Kiuchi; Jan K. Ho; Janis Marc Nolde; Leslie Marisol Lugo Gavidia; Revathy Carnagarin; Vance B. Matthews; Markus P. Schlaich; Markus P. Schlaich; Markus P. Schlaich (Frontiers in Physiology, 2020)
Studies have revealed a robust and independent correlation between chronic kidney disease (CKD) and cardiovascular (CV) events, including death, heart failure, and myocardial infarction. Recent clinical trials extend this range of adverse CV events, including malignant ventricular arrhythmias and sudden cardiac death (SCD). Moreover, other studies point out that cardiac structural and electrophysiological changes are a common occurrence in this population. These processes are likely contributors to the heightened hazard of arrhythmias in CKD population and may be useful indicators to detect patients who are at a higher SCD risk. Sympathetic overactivity is associated with increased CV risk, specifically in the population with CKD, and it is a central feature of the hypertensive state, occurring early in its clinical course. Sympathetic hyperactivity is already evident at the earliest clinical stage of CKD and is directly related to the progression of renal failure, being most pronounced in those with end-stage renal disease. Sympathetic efferent and afferent neural activity in kidney failure is a crucial facilitator for the perpetuation and evolvement of the disease. Here, we will revisit the role of the feedback loop of the sympathetic neural cycle in the context of CKD and how it may aggravate several of the risk factors responsible for causing SCD. Targeting the overactive sympathetic nervous system therapeutically, either pharmacologically or with newly available device-based approaches, may prove to be a pivotal intervention to curb the substantial burden of cardiac arrhythmias and SCD in the high-risk population of patients with CKD.